Capabilities of a mobile extracorporeal membrane oxygenation service for severe respiratory failure delivered by intensive care specialists2. (26th February 2015) - Sherren, P. B.; Shepherd, S. J.; Glover, G. W.; Meadows, C. I. S.; Langrish, C.; Ioannou, N.; Wyncoll, D.; Daly, K.; Gooby, N.; Agnew, N.; Barrett, N. A.
Summary We conducted a single‐centre observational study of retrievals for severe respiratory failure over 12 months. Our intensivist‐delivered retrieval service has mobile extracorporeal membrane oxygenation capabilities. Sixty patients were analysed: 34 (57%) were female and the mean (SD) age was 44.1 (13.6) years. The mean (SD) PaO2/FIO2 ratio at referral was 10.2 (4.1) kPa and median (IQR [range]) Murray score was 3.25 (3.0–3.5 [1.5–4.0]). Forty‐eight patients (80%) required veno‐venous extracorporeal membrane oxygenation at the referring centre. There were no cannulation or extracorporeal membrane oxygenation‐related complications. The median (IQR [range]) retrieval distance was 47.2 (14.9–77.0 [2.3–342.0]) miles. There were no major adverse events during retrieval. Thirty‐seven patients (77%) who received extracorporeal membrane oxygenation survived to discharge from the intensive care unit and 36 patients (75%) were alive after six months. Senior intensivist‐initiated and delivered mobile extracorporeal membrane oxygenation is safe and associated with a high incidence of survival.